Acceptance Analysis of the Core Tax Using the UTAUT Model: A Study on Individual Taxpayers in Palu City - RIDWAN, Muhammad; MASRUDDIN, M; JAMALUDDIN, J; ZAHRA, Femilia; ERWINSYAH, E (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the level of acceptance of the Coretax information system from the perspective of individual taxpayers in Palu City. Using the Unified Theory of Acceptance and Use of Technology (UTAUT) model with a final sample of 105 respondents. Data collection was conducted using a questionnaire method, and the results were processed using SPSS version 26 for statistical data analysis. The results of this study indicate that performance expectations and social interactions significantly influence interest in using Core Tax, while effort expectations and facilitating conditions do not significantly influence interest in using Core Tax. The results of this study reinforce the importance of continuously improving the development of tax information systems in Indonesia so that the system can facilitate taxpayers, especially individuals, in fulfilling their tax obligations. As a suggestion for further research, the influence of other variables, such as user habits and hedonic motivations, on the intention to use Coretax can be further studied to complexify the findings of the research on Coretax use.